Electrical conductivity in salt-polymer solutions / Hussein Hanibah - Hanibah, Hussein (2011)
Electrolytic conductivity (/c) at 25.0 °C was measured in liquid electrolyte and liquid polymer electrolyte as a function of salt concentration (Csait) by AC conductivity meter. The effect of adding polymer into liquid electrolyte was discussed. Molar conductivity at infinite dilution (Ao) of weak electrolyte lithium perchlorate (LiC104) in tetrahydrofuran (THF) and acetronitrile (ACN), respectively was estimated from Ostwald's dilution law. The estimated Ao values for both LiC104 in THF and LiC104 in ACN are 76 and 24200 S cm2 mol"1 . The expected values for both systems are 155.3 ± 2.0 and 173.0 ± 2.0 S cm2 mol"1 . The limitation of Oswald's dilution law in estimation of Ao values for weak electrolytes is demonstrated in this study. We propose, a double-logarithmic plot of K versus Csait (power law) was introduced to determine the Ao for weak electrolytes. The power law proposed is linear for certain (finite) range of Csait . The reference salt concentration (Cref) of the systems has to be estimated carefully. It is noted that, Cref for each system that corresponding to the Ao is approximately half of the lowest Csait concentration that still obeys the power law before the data starts to divert from the linearity of the power law. In order to estimate Ao value at 25.0 °C for LiC104 in polyethylene oxide) (PEO) solution (PEO + ACN), Cref = 3.0-10"9 mol cm"3 is adopted. PEO with different molecular weights, Mn$ = 3-105 , 6-105 , 1-106 and 4-106 g mol"1 were studied and are denoted as PEOi , PEO2 , PEO3 and PEO4 respectively. The K of the LiC104 in PEO solutions was measured as a function of Csait. The PEO solutions comprise of fixed PEO concentrations (CPE0) of PEO,, PE02, PE03 and PE04 from 0.0005 to 0.010 g cm" 3 . In general, as CPEOS increase for LiC104 in PEO solution's, Ao values of the systems tend to show a descending trend. It is also noted, higher Mn of PEOs at CPEO - constant demonstrate a descending tendency in Ao. This indicates lower ion mobility (IC) in the electrolyte as calculated in this study. Finally, the degree of dissociation (a) for LiC104 in PEO solution was calculated as a function of Csait for different PEOs at different CPEOS. Higher Mn PEOs result in the improvement of dissociation of LiC104 in PEO solutions as compared to UCIO4 in ACN. At CPEO = constant, a values are insignificantly different at higher CPEO